Pengembangan Rencana Pembelajaran Pendidikan Agama Islam Berbasis Nilai Karakter Islami dalam Konteks Sekolah Inklusif - Wiwin Winarti; Sansan Saefumillah; Yayah Hoeriyah; Muhammad Khildan Khoirul Amal; Elsa Salsabilah (Attractive : Innovative Education Journal, 2025)
Islamic Religious Education plays a crucial role in shaping students' morals and character, particularly in the face of the challenges posed by globalization. As a discipline centered on cultivating ethical values, it serves as a fundamental instrument for instilling Islamic character principles in students. This study aims to develop an Islamic Religious Education learning framework that integrates Islamic character values within an inclusive school setting, with an emphasis on adaptive and effective implementation strategies. Employing a qualitative approach, this research utilizes a case study method conducted at SMP IT Manbaul Ulum. Data collection involved in-depth interviews with school principals and teachers, as well as classroom observations. The findings indicate that while teachers strive to integrate Islamic values such as honesty, responsibility, and tolerance into their instruction, they face significant challenges due to limited resources and inadequate training. To accommodate student diversity, teachers employ strategies such as prophetic storytelling and group discussions; however, they report a lack of sufficient professional development in managing inclusive classrooms effectively. Furthermore, the school principal underscores the need for specialized training programs to enhance teachers' competencies in integrating Islamic values within an inclusive educational framework. The implications of this study highlight the necessity of enhancing teacher training, diversifying educational resources, and developing accessible learning media to ensure that Islamic values-based education is effective and inclusive for all students, including those with special needs.